Sleep quality and its psychological correlates among university students in Ethiopia: a cross-sectional study - Lemma, Seblewngel (BioMed Central, 2012)
BACKGROUND: Sleep is an important physiological process for humans. University students in most resource limited countries often report poor sleep quality due to changing social opportunities and increasing academic demands. However, sleep quality among university students has not been studied in Ethiopia. Thus, this study assessed sleep quality and its demographic and psychological correlates among university students. METHODS: A cross-sectional survey was conducted in two universities in Ethiopia. Multistage sampling procedures were used to enroll 2,817 students into the study. A self-administered structured questionnaire including the Pittsburgh Sleep Quality Index (PSQI), the Depression Anxiety Stress Scale-21, the Perceived Stress Scale (PSS) and selected modules of the World Health Organization STEPS instrument was used for the study. This research included 2,551 students. Frequency, median, mean with standard deviation and 95% confidence interval were used to characterize sleep quality and other variables. Analysis of variance and binary logistic regression procedures were also used. RESULT: The prevalence of poor sleep quality (total PSQI score > 5) was 55.8% (1,424). Female students (adjusted odds ratio (AOR) 1.23; 95% CI: 1.00, 1.57), second year (AOR 2.91; 95% CI: 2.1, 4.02) and third year students (AOR 2.25; 95% CI 1.62, 3.12) had statistically significant higher odds of poor sleep quality. Perceived stress level and symptoms of depression and anxiety were strongly associated with sleep quality. CONCLUSION: A substantial proportion of university students are affected by poor sleep quality. If our results are confirmed in prospective studies, health promotion and educational programs for students should emphasize the importance of sleep and mental health.